PERENCANAAN ALAT PENGOLAH LIMBAH BUAH NANAS MENJADI BIOETANOL DENGAN METODE SUBLIM ELECTRIK - Mohamad Yahya Al Fajar (UNIVERSITAS ISLAM MALANG, 2019)
Indonesia is a big country in the Asian continent, not only that Indonesia also has the largest pineapple garden after Thailand. Pineapple is a fruit that contains sugar and carbohydrate levels such as cassava, rice, wheat, etc. which are usually used for making ethanol. Besides making tools there are many other ways to examine the processes of heat transfer, and steam analysis. This time the researcher wants to do a simulation experiment using a software to analyze a steam displacement and heat transfer that occurs in a simple steam boiler to make it happen, so some processes need to be done starting from designing, determining materials and materials, and several dimensions to calculate the dimensions. created a design that approached the original tool. In planning this distillation boiler uses a simulation with Computational Fluid Dynamic (CFD) Software. From the results of planning and calculation one conclusion can be drawn, Distillation type = Distillation with water and steam, Steam capacity = 0.05474 kg / s, Inlet pressure = 6 bar = 87 lb / in2, Maximum Allowable stress value = 11 ksi = 1100 lb/in2, Steam temperature in the distillation kettle = 164.4oC, The steam temperature exits the distillation kettle = 56oC. The average temperature at the stainless steel pipe outlet after passing through the condenser= 25oC = 289,15 oK, So the heat transfer rate of each ft2 is 393.2 BTU / hft2.